Creating American Reform Judaism : the Life and Times of Isaac Mayer Wise. - Temkin, Sefton D. (Littman Library of Jewish Civilization, The, 1998)
Sefton Temkin has provided us with a much-needed critical and balanced portrayal of Wise ... The best scholarly work on Wise to date. It presents an admiring yet critical picture of Wise's achievements and personality ... a welcome contribution to our understanding of the man and his times.' George L. Berlin, AJS Review 'Thorough and extremely competent ... Temkin contributes a great deal through his careful use of materials ... The book will be of interest to general readers ... who wish not only to understand Isaac Mayer Wise but, moreover, to comprehend the attitudes and events that led to the f.